BIMBINGAN DAN KONSELING ISLAM SEBAGAI UPAYA PENCEGAHAN PADA MARRIED BY ACCIDENT (Jurnal Bimbingan dan Konseling Islam, 2013)
In this era, we have heard several times the incidence of Married by Accident (unwed). Teenagers usually do not know in depth the impact of Married by Accident, so, they do not know the effort or effective way to prevent it. This paper raised about the Islamic Guidance and Counselling plays an important role in providing guidance on how to determine the impact of Married by Accident and their prevention efforts. Thus, in the process of Islamic Guidance and Counselling using self awareness techniques is expected to make teens aware of and can minimize the incidence Married by Accident in adolescents. The method used in this study is the method of Reseach & Developmental research, types of research development. Results of Islamic Guidance and Counseling with self awareness techniques declared successful with a percentage of 89.24%.Keywords: Islamic Guidance and Counseling, Married by Accident